Need for institutional impact assessment in planning irrigation system modernization - Bandaragoda, Don Jayatissa (International Water Management Institute, 1998)
Presents a case study of the institutional implications of remodeling an old irrigation system in northern Pakistan. Highlights the importance for donors and project planners to consider institutional issues such as water allocation rules, operation procedures, and organizational capacity for post-construction system management along with changes to the physical infrastructure.